Mirovoj slalom v zerkale XiX Olimijskikh igr-2002 mezhdu tekhnikoj povorotov i tekhniki skolzheniya - Oshchepkov, G. G. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The article is about technique and biomechanics in slalom. The basis for this work are works of the author about this subject for many years.